Poás volcano: Geophysical-Geochemical signatures and dynamics of its magmatic-hydrothermal system - Martínez Cruz, María (2014)
Poás volcanic complex hosts a hyper-acid lake where geochemical signatures are related to two major controlling processes: (a) The level of inux and dissolution-hydrolysis of magmatic volatiles in a sub-surface hydrothermal reservoir forming extremely acidic brines, and (b) The amount of partial or wholesale dissolution of rock, enriching the waters in rock-forming elements. This combined uptake of magmatic volatiles and water-rock interaction makes the Poás lake-hydrothermal system one of the most dynamic and chemically extreme aqueous environments on Earth [1]. This study provides some datasets of the most salient geochemical signatures of the acid lake and their strongly uctuating behaviour observed over the last ca. 30 years. These signatures are investigated to a) Explore the nature and extent of compositional changes and ux of magmatic volatiles released from a shallow magma reservoir, and b) Gain insights into the modulating eects of the hydrothermal system underlying the acid lake to constraint a model for the Poás lake-hydrothermal system.